What particle verbs have to do with grammatical aspect in early child English - Jeschull, Liane (ZAS Papers in Linguistics, 2003)
The current study investigates the relation between aspect and particle verbs in the acquisition of English. Its purpose is to determine whether children associate telicity, as argued in previous studies, or rather perfectivity, which entails completion of a telic situation, with their early particle verb use. The study analyzes naturalistic data of four monolingual children between 1;6 and 3;8 from CHILDES acquiring English as their first language. On the one hand, it finds that children use both –ed and irregular perfective morphology with simplex verbs before particle verbs. They further use imperfective before perfective morphology with particle verbs. These findings suggest that there is no correlation between telic particle verbs and perfective morphology, as would have been predicted on an account which claims that lexical aspect of predicates guides the acquisition of grammatical aspect (Olsen & Weinberg 1999). On the other hand, the study finds that the children’s particle verbs denote telic situations from early on, but not half of them were used to refer to situations that are also completed. This finding questions analyses which claim that, at an initial stage, children will only interpret predicates as telic if they refer to situations that are at the same time completed. Completion information is not necessary for children in order to use particle verbs correctly for telic situations, as would have been predicted on an extended account along the lines of Wagner (2001). As a conclusion, it is suggested that the divergent findings result from a difference in methodology. While restrictions of perfective and imperfective morphology to particular classes of lexical aspect pertain to the production of grammatical aspect morphology, perfective and imperfective viewpoints on situations pertain to the level of interpretation of telic and atelic situations.